2015
DOI: 10.1039/c4bm00319e
|View full text |Cite
|
Sign up to set email alerts
|

Media additives to promote spheroid circularity and compactness in hanging drop platform

Abstract: Three-dimensional spheroid cultures have become increasingly popular as drug screening platforms, especially with the advent of different high throughput spheroid forming technologies. However, comparing drug efficacy across different cell types in spheroid culture can be difficult due to variations in spheroid morphologies and transport characteristics. Improving the reproducibility of compact, circular spheroids contributes to standardizing and increasing the fidelity of the desired gradient profiles in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 28 publications
8
63
0
6
Order By: Relevance
“…Two weeks after implantation, mice were treated with rhCCN6 (1ng/g, i.v., twice a week) or BSA (1ng/g) in the same regimen, and followed by palpation and caliper measurements for 3 weeks. Organoids derived form MMTV-Cre; Ccn6 fl/fl mice tumors were generated following previous reports [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Two weeks after implantation, mice were treated with rhCCN6 (1ng/g, i.v., twice a week) or BSA (1ng/g) in the same regimen, and followed by palpation and caliper measurements for 3 weeks. Organoids derived form MMTV-Cre; Ccn6 fl/fl mice tumors were generated following previous reports [20]. …”
Section: Methodsmentioning
confidence: 99%
“…These plates have been used to generate human epithelial carcinoma spheroids, prostate cancer spheroids as well as non-cancer primary stem- and progenitor cell spheroids [14, 15]. Recently, Leung et al demonstrated that the spheroids generated using hanging drop array platforms demonstrate excellent circularity and compactness [16]. …”
Section: Introductionmentioning
confidence: 99%
“…The MDA-MB 231 cells used for this portion of the study do not spontaneously form tight spheroids 22 , enabling us to simulate a 2D slice of a spheroid in a 3D culture-like environment. Employing a prevalent practice for the qualification of bioreactors 35 , we generated a computational model of oxygen supply, diffusion, and uptake (Figure 3) by using the geometry of the experimental system and a range of literature values of oxygen V max and K m 36–42 to run a parametric sweep.…”
Section: Discussionmentioning
confidence: 99%
“…Spheroids were generated using high-throughput hanging-drop-array plates 21 and the culture methods recently presented 22 . Prior to use, a hydrophilic coating was applied onto the entire surface of the hanging-drop plate by soaking the plate overnight in 0.1%, Pluronic F108.…”
Section: Methodsmentioning
confidence: 99%